Overview of Constipation in Children - Yoseph Arif Putra; Feby Febriana (Cermin Dunia Kedokteran, 2016)
Constipation is very common, the prevalence varies from 0.07%-29.6%. The prevalence of functional constipation in children ranges from 4-36%, up to one third of children ages 6 to 12 years are reported to have constipation. Constipation generally first appears between the ages of two and four years. The cause is usually non –organic in about 90% cases. The most widely accepted definitions for childhood functional constipation is Rome III definitions. The symptoms include infrequent stools, pain, soiling, stool withholding maneuvers, blood in stools, enuresis and other urinary symptoms. The differential diagnosis is divided into two large groups, intraabdominal and extraabdominal. Constipation is diagnosed by history, physical examination and clinical investigation. Treatment should include disimpaction and maintenance.Konstipasi adalah gejala sangat umum, baik di pelayanan kesehatan lini pertama maupun kedua, prevalensinya 0.07 % - 29.6 %. Prevalensi konstipasi fungsional pada anak berkisar 4-36%. Lebih dari sepertiga anak-anak usia 6-12 tahun dilaporkan menderita konstipasi. Konstipasi biasanya muncul pertama kali antara usia dua dan empat tahun. Penyebab non organik pada lebih dari 90% kasus. Definisi yang paling sering dipakai adalah definisi Rome III. Gejala-gejalanya adalah buang air besar tidak rutin, nyeri, soiling, manuver menahan buang air besar, darah pada feses, tidak dapat menahan berkemih dan gejala berkemih lainnya. Diagnosis banding terdiri dari dua kelompok besar, intraabdomen dan ekstrabdomen. Konstipasi didiagnosis dengan anamnesis, pemeriksaan fisik dan pemeriksaan penunjang. Penatalaksanaan termasuk disimpaksi dan terapi pemeliharaan.